PENGARUH PEMBERIAN LEGIN DAN PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max (L.) Merril) - Sari, Eka Febriana; Puspitorini, Palupi; Kurniastuti, Tri (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2016)
The research aims to determine of the effect application legin and urea fertilizer to growth and result of soybean (Glycine max (L.) Merr.). The research held in June until August 2016 in the Menjangan Kalung, Slorok village, Garum, Blitar. This research used method was Split Split Plot Randomized Block Design factorial pattern of two factors and three replications. This first factor was dose legin (L) consisted three level namely : dose 3 g kgË‰Â¹ (L1), dose 5 g kgË‰Â¹ (L2), and 7 g kgË‰Â¹(L3). The second factor was dose urea fertilizer (U) consisted four level namely : Without urea fertilizer (U0), 10 kg haË‰Â¹(U1), 20 kg haË‰Â¹(U2), and 30 kg haË‰Â¹(U3). Observation parameters is plant height, number of leaves, the number of nodules, number of pods, number of empaty pods, number of pods, and dry weight of 100 seed. Data were analyzed with used analysis of variance , if take effect fellowed with LSD. Research result to show that: 1)The best interaction is teratment combination L2U2 that don ’t real different with treatment L2U3, L2U1 and L2U0. 2) Application doselegin 5 g kgË‰Â¹ in alone is the best treatment that result highest averagely with percentage 25.48% appealed with application dose legin 3 g kgË‰Â¹ and 7 g kgË‰Â¹. 3) Application doselegin 5 g kgË‰Â¹ in alone is the best treatment that result highest averagely with percentage 6.58% appealed with application dose fertilizer urea 0 kg haË‰Â¹, 10 kg haË‰Â¹ and 30 kg haË‰Â¹.